Relationship between Socioeconomic Demographic Characteristics with Antibiotic Self-Medication in Community Dwelling Adults - Michael Aditya; Istriati Istriati; Aih Cahyani (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Infectious diseases escalation in developing countries especially in Indonesia lead to increasing use of antibiotics in the community. Self-medication with antibiotics may increase the risk of resistant bacteria and irrational use of antibiotics. This study was conducted to determine the relationship between socioeconomic -demographic characteristics with antibiotic self-medication. Methods: An analytical cross sectional study was conducted on people from Sayang Village in West Java Indonesia aged over 18 years and had experience in using antibiotics. A total of 146 respondents were selected as the sample of this study. A validated questionnaire was used to collect data. Data were analysed by using descriptive statistics and Chi-Square test to analyze the relationship between socioeconomic demographic characteristics with antibiotic self-medication.Results: Out of 146 questionnaires that were completed, 111 were female and 35 male respondents, 75 respondents had experience in using antibiotics without prescription. The survey showed significant relation between antibiotics use with monthly income (p=0,031) and source of income (p=0,009).Conclusions: The study confirms that there is relation between monthly income and source of income with antibiotic self-medication. [AMJ.2017;4(1):73–7]DOI: 10.15850/amj.v4n1.1023